The Effect of Starter Culture on Increasing Food Safety and Its Impact on Customer Preference - Hillary Ellen Yapradinata; Alvin Chandra Wijaya; Tuhfah Wikaputra; Masdiana Cendrakasih Padaga; Oki Krisbianto (Berkala Ilmiah Pertanian, 2025)
Aron is a fermented white corn, a traditional product of the Tengger tribe, which is susceptible to contamination by pathogenic microorganisms during its production process. The addition of starter cultures obtained from the isolation of dominant lactic acid bacteria in the natural fermentation of white corn, namely Lactobacillus and Streptococcus, was expected to inhibit the growth of pathogenic microorganisms. The aim of this study was to evaluate the ability of different concentrations of starter culture, starting from 0%, 10%, 20%, and 30% to inhibit the growth of pathogenic microorganisms, under different fermentation conditions, which are traditional fermentation at a cold temperature around 13-18°C in Tengger and controlled fermentation at 28-32°C in a laboratory in Surabaya for 6 days, with analysis done on days 0, 3, and 6. Differences in sensory characteristics of aron with the addition of starter cultures, including aroma, taste, and color, were also evaluated. The indicator used to measure the growth of pathogenic microorganisms was Enterobacteriaceae, which quantity was analyzed to evaluate the inhibition of its growth by lactic acid bacteria under both conditions. Biochemical analyses such as TSIA test, catalase test, and motility test were performed to ensure that the dominant bacteria at the end of fermentation were lactic acid bacteria. Additionally, molds that grew during fermentation in both conditions were identified. Sensory analysis was done at the end of fermentation, including aroma, taste, and colour tests, which supported by Whiteness Index, DE2000, and Chroma analyses to evaluate the impact of starter culture and environmental conditions on the resulting aron. The addition of starter cultures was shown to affect the inhibition of Enterobacteriaceae growth under both conditions. Biochemical tests serve as supporting evidence that the dominant bacteria under both conditions after 6 days of fermentation were lactic acid bacteria. Aroma was identified as an attribute likely influenced by the addition of starter culture and environmental differences, caused by the compounds produced during fermentation. It was concluded that the addition of starter culture and environmental differences affect the microbiological characteristics and aroma of aron.